Prevalence and characteristics of eye involvement in patients with rheumatoid arthritis - Fadhil, Ruba Abbas; Al-Dabbagh, Khalid A. (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Rheumatoid arthritis is a systemic inflammatory disease. Ocular manifestations involved with rheumatoid arthritis are keratoconjunctivitis sicca, episcleritis, scleritis, anterior and posterior uveitis, dry eyes and ulcerative keratitis. This study aimed to detect the prevalence of ocular manifestations in rheumatoid arthritis patients, find out the relation between the effects of disease modifying anti-rheumatic drugs, biological agents and ocular complications in rheumatoid arthritis patients and explore role of anti-cyclic citrullinated peptide antibodies. Methods: This is a cross-sectional clinical study of 60 rheumatoid arthritis patients who have attended Rizgary Teaching Hospital in Erbil. A data information about symptoms of ocular manifestations and history of ocular complications before starting disease modifying anti-rheumatic drugs and/or biological agents were taken. Musculoskeletal examination, serum Anti-CCP antibodies test were done. Ocular examination by ophthalmologist was done. Results: This study was conducted from April to November 2015 and involved 60 patients; 55 females and five males with a mean± SD age of 46 ± 11.46 years. Thirty nine (65%) patients had ocular manifestations of rheumatoid arthritis. The most frequent manifestation was dry eyes 30 (50.0%). There was no relation between severity of the rheumatoid arthritis disease and ocular manifestation (P = 0.529). There was a relationship between the Anti-CCP antibodies titer and presence of ocular manifestations in rheumatoid arthritis patients (P = 0.006). There were no curable effects of the disease modifying anti-rheumatic drugs, biological agents on ocular manifestations in rheumatoid arthritis patients (P = 0.787). Conclusion: Dry eye was the most common ocular manifestation, anti-CCP antibodies are a sensitive marker for ocular manifestations. Disease modifying anti-rheumatic drugs and biological therapies provide no significant efficacy in treatment or prevent the occurrence of ocular manifestations in rheumatoid arthritis patients.